A dangerous idea : the Alaska Native Brotherhood and the struggle for Indigenous rights - Metcalfe, Peter, 1951- (University of Alaska Press, 2014)
"Decades before the marches and victories of the 1960s, a group of Alaska Natives were making civil rights history. Throughout the early twentieth century, the Alaska Native Brotherhood fought for citizenship, voting rights, and education for all Alaska Natives, securing unheard-of victories in a contentious time. Their unified work and legal prowess propelled the Alaska Native Claims Settlement Act, one of the biggest claim settlements in United States history. A dangerous idea tells an overlooked but powerful story of Alaska Natives fighting for their rights under American law and details one of the rare successes for Native Americans in their nearly two-hundred-year effort to define and protect their rights"--